The Existence of Among Among Lahiran in Jorong Sungai Lambai Nagari Lubuk Gadang Selatan District South Solok Province West Sumatra - ikhsan, Dipo; Febri Yulika; Edi Satria (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This study discusses the existence of Among-among birth in Jorong Sungai Lambai, Lubuk Gadang Selatan, South Solok Regency. The purpose of this study is to find out how the existence of the Among-among tradition and also the procedures for implementing the Among-among tradition in the Lambai River area. The theories used in this study are existentialism and structural functional theories. The existence of Among-among tradition in the community so that it can survive until now in the midst of modern society. The method used is qualitative research with an ethnographic approach. Data collection techniques are observation, interviews, literature studies, and documentation. . The findings in this study are that the Lambai River community carries out the Among-among tradition of birth with an uncomplicated process, the conditions in its implementation are so easy to find around their residence. The existence of this tradition is very meaningful for the community for further survival.